2021
DOI: 10.1186/s40168-020-00975-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fluorescent glycan uptake to elucidate strain-level variability in foraging behaviors of rumen bacteria

Abstract: Gut microbiomes, such as the microbial community that colonizes the rumen, have vast catabolic potential and play a vital role in host health and nutrition. By expanding our understanding of metabolic pathways in these ecosystems, we will garner foundational information for manipulating microbiome structure and function to influence host physiology. Currently, our knowledge of metabolic pathways relies heavily on inferences derived from metagenomics or culturing bacteria in vitro. However, novel approaches tar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…In general, the expression of large enzymatic repertoires can impede growth, as less resources are allocated to biomass production (Basan et al, 2015). Therefore, we expect phenotypic heterogeneity to play a significant role in populations carrying large enzyme repertoires, such as the Verrucomicrobia that target fucoidan (Sichert et al, 2020) or Bacteroidetes that need to coordinate large number of PULs (Klassen et al, 2021a). Overall, the potential benefits of these forms of phenotypic heterogeneity represent an exciting frontier in the study of polysaccharide-bacteria interactions.…”
Section: Challenge 3 | Sensing Regulation and Phenotypic Heterogeneitymentioning
confidence: 99%
“…In general, the expression of large enzymatic repertoires can impede growth, as less resources are allocated to biomass production (Basan et al, 2015). Therefore, we expect phenotypic heterogeneity to play a significant role in populations carrying large enzyme repertoires, such as the Verrucomicrobia that target fucoidan (Sichert et al, 2020) or Bacteroidetes that need to coordinate large number of PULs (Klassen et al, 2021a). Overall, the potential benefits of these forms of phenotypic heterogeneity represent an exciting frontier in the study of polysaccharide-bacteria interactions.…”
Section: Challenge 3 | Sensing Regulation and Phenotypic Heterogeneitymentioning
confidence: 99%
“…This study demonstrated that FLA-PS can be used to correlate metabolic phenotypes with genotypes and to differentiate between foraging strategies (Grondin et al, 2017). More recently, FLA-PS were successfully used in combination with FISH to detect and identify metabolically active cells in rumen community, respectively, and to quantify differences in glycan uptake rates between Bacteroides strains (Klassen et al, 2021).…”
Section: Fla-ps In Gut Microbiome Researchmentioning
confidence: 85%
“…Use of 2-NBDG and similar monosaccharide probes is limited, however, because transport proteins are typically unable to accommodate the bulky fluorophore and transport it into the cell. In contrast, fluorescently labeled polysaccharides (FLA-PS) (Glabe et al, 1983) provide more flexibility to study substrate uptake, and have been very successful when fluoresceinamine is used as the conjugate fluorophore (Figure 2D; Reintjes et al, 2017;Hehemann et al, 2019;Klassen et al, 2021). In contrast to methods that only label the reducing end, using a stochastic method to label hydroxyl groups of monosaccharide residues generates a library of related probes that are sampled by enzymes and transporters (Figure 2E); probes that are amenable to importation can be visualized by fluorescence microscopy (Figure 2F).…”
Section: Next-generation Physiology To Identify the Function Of Single Cells Visualizing Microbiome-carbohydrate Interactions With Carbohmentioning
confidence: 99%
“…The rumen is a complex microbial anaerobic fermentation chamber that harbors one of the most diverse intestinal microbial communities of the animal kingdom ( Li et al, 2021 ). In terms of quantity and variety, bacteria are the dominant species in the rumen, and the catabolic potential of ruminal bacteria plays a vital role in the health and nutrition of their host ( Klassen et al, 2021 ). Higher microbial diversity in the mammalian gastrointestinal system often equates with stronger metabolic capacity and stability ( Li et al, 2019 ), such as Plateau pika ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%